2019
DOI: 10.1097/md.0000000000015953
|View full text |Cite
|
Sign up to set email alerts
|

Association between gene variants and the recurrence of atrial fibrillation

Abstract: Background: Studies showed the controversial results about the effect of common genetic polymorphisms on the atrial fibrillation (AF) recurrence. We performed the systematic review and meta-analysis to qualify the association between common genetic polymorphisms and AF recurrence. Methods: Articles were systematically retrieved PubMed, Web of Science, EMBASE, Wanfang, and CNKI database and 9 studies including 3204 patients were enrolled in our meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Choi et al [27] found no correlation between SNP rs2106261 and postoperative recurrence in patients with atrial fibrillation in a study of 1068 patients with atrial fibrillation undergoing radiofrequency ablation in a Korean population. A meta-analysis by Jiang et al [43] reached the same conclusion.…”
Section: Zfhx3 Snp Rs2106261mentioning
confidence: 62%
“…Choi et al [27] found no correlation between SNP rs2106261 and postoperative recurrence in patients with atrial fibrillation in a study of 1068 patients with atrial fibrillation undergoing radiofrequency ablation in a Korean population. A meta-analysis by Jiang et al [43] reached the same conclusion.…”
Section: Zfhx3 Snp Rs2106261mentioning
confidence: 62%
“…Zhai et al performed a meta-analysis of 10 case-control comparisons about rs7193343 polymorphism and found this polymorphism may be associated with risk of AF in the Caucasian population but not in the Asian population [ 44 ]. In addition, Jiang et al also focused the polymorphisms for AF susceptibility through meta-analysis, and two polymorphisms in the ZFHX3 gene were analyzed (three studies about rs7193343 and only two studies about rs2106261), and no association was observed [ 45 ]. After that, other studies related to ZFHX3 gene rs2106261 polymorphism have been reported; moreover, another gene polymorphism (PRRX1 rs3903239) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed contentious ndings on the impact of common genetic variants on the recurrence of atrial brillation (AF) [8][9][10][11][12][13]. A recent meta-analysis found that rs2200733 and rs10033464 on chromosome 4Q25 (near PITX2) were associated with the risk of AF recurrence [14]. Zhang et al investigated the possibility that the aldosterone synthetase (CYP11B2) gene − 344T/C polymorphism and the angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) could affect the risk and recurrence of isolated atrial brillation (AF).…”
Section: Introductionmentioning
confidence: 99%